Analisis Titik Lokasi Kecelakaan di Ruas Jalan Tol Palimanan – Kanci - Widyaningrum, Shiska Wahyu; Fahmi, Silvia Afida; Fadillah, Ali; Budiyanto, Daffa Ramadhan Eka; Basuki, Ahmad (IAI Nasional Laa Roiba Bogor, 2025)
Traffic accidents on toll roads, including the Palimanan – Kanci (Palikanci) Toll Road, are a major concern due to high vehicle volume and other factors such as driver fatigue, weather conditions, and compliance with traffic regulations. This study aims to identify accident-prone locations and formulate mitigation measures. The research employs a quantitative analysis method using both primary and secondary data. Based on accident location identification for the Palimanan – Kanci Toll Road from 2022 to 2024, using the Equivalent Accident Number (EAN) and Upper Control Limit (UCL) methods per 1 km, 11 accident-prone locations were identified. However, two locations had the highest accident rates: Lane A at KM 210 – 211 and Lane B at KM 195 – 196. The most common cause of accidents was driver inattention and drowsiness, with the predominant accident type being rear-end collisions. The result of this study can serve as a reference for mitigation efforts to reduce accidents on the Palimanan – Kanci Toll Road.